Sensibilité des populations d’ Aedes Aegypti vis-à-vis des organochlorés, pyréthrinoïdes et des carbamates dans la commune de Natitingou au Nord-Est du Bénin - Anges, Yadouleton; Jean-Robert, Klotoe; Christophe, Chabi; Ramziyath, Agbanrin; Carine, Tchibozo; Achaz, Agolinou; Roland, Tossou; Lamine, Baba-Moussa (European Scientific Journal, ESJ, 2018)
Insecticide treatments for crop protection have often be cited as the main factor of the resistance selection of Aedes aegypti. This is however the main vector dengue fever. To verify this hypothesis, bioassay tests was performed on adults collected from the field (2 urban and 2 rural areas) at Natitingou to assess the susceptibility of dengue vectors to insecticideimpregnated papers (permethrin 0.75%, delthamethrin 0.05%, lambdacyalothrin 0.05%, DDT 4%, and bendiocarb 0.1%) following WHO Pesticide Evaluation Scheme. Results from this study showed that Ae. Aegypti populations were resistant to DDT and pyrethroids with 12% and 38% respectively as mean of mortality despite the areas of mosquitoes collection. However, they were fully susceptible to bendiocarb. Our study showed that Aedes aegypti populations had developed resistance to organochlorine and pyrethroids, but are susceptible to carbamate. The low mortality rate recorded in all populations of Ae. Aegypti with bendiocarb is encouraging in regards to the use of this insecticide as an alternative in case of outbreak of dengue fever in this district of Benin.